Pelatihan Tindakan Kelas Berbasis Student-Centered Learning untuk Meningkatkan Profesionalisme Guru Sekolah Indonesia Kuala Lumpur - Siti Sri Wulandari; Waspodo Tjipto Subroto; Susanti Susanti; Dwi Yuli Rahmawati; Luqman Hakim; Norida Canda Sakti; Retno Mustika Dewi; Meylia Elizabeth Ranu; Agung Listiadi (IKIP PGRI Bojonegoro, 2025)
One of the Indonesian Schools Abroad (SILN) is Sekolah Indonesia Kuala Lumpur (SIKL) which was established on July 10, 1969, located at Jalan No. 1 Lorong Tun Ismail 50480, Federal Territory of Kuala Lumpur Malaysia. SKIL consistently takes part in providing educational services to the Indonesian people in Malaysia which refers to the basis of national education.The profile conditions of the target group provide an overview that the potential teachers at SIKL are already bachelors and the majority are already civil servants, making it easier to be improved and empowered to be more potential and professional. The objectives of the implementation of Community Service (PKM) are 1) The implementation of PTK for teachers using the innovative Student Centered Learning (SCL) learning model. 2) PTK produces an active and interactive learning process so that learning is more interesting and not boring. The implementation method uses aspects of knowledge through the PTK module, Aspects of Skills through the practice of drafting PTK, Implementation Evaluation. The result of the implementation of PKM is that teachers can apply strategies or learning models of Student Centered Learning (SCL). SCL-based PTK practice can improve the quality of learning. The understanding of participants in identifying problems, formulating learning problems, compiling literature reviews, PTK cycles, PTK Methods, and steps in determining the conclusion of PTK is good. Participants were very enthusiastic from the beginning to the end in the process of making a draft PTK proposal for the implementation of PKM, namely teachers can apply strategies or learning models of Student Centered Learning (SCL). SCL-based PTK practice can improve the quality of learning. The understanding of participants in identifying problems, formulating learning problems, compiling literature reviews, PTK cycles, PTK Methods, and steps in determining the conclusion of PTK is good. Participants were very enthusiastic from the beginning to the end in the process of making a draft PTK proposal. Salah satu Sekolah Indonesia yang berada di Luar Negeri (SILN) adalah Sekolah Indonesia Kuala Lumpur (SIKL) yang didirikan pada 10 Juli 1969, beralamat di jalan No. 1 Lorong Tun Ismail 50480, wilayah Persekutuan Kuala Lumpur Malaysia. SKIL konsisten berkiprah memberikan pelayanan pendidikan kepada masyarakat Indonesia di Malaysia yang mengacu pada dasar pendidikan nasional. Kondisi profil kelompok sasaran memberikan gambaran bahwa potensi guru di SIKL tersebut telah sarjana dan mayoritas sudah PNS, sehingga memungkinkan lebih mudah untuk ditingkatkan dan diberdayakan menjadi lebih potensial dan profesional. Tujuan pelaksanaan Pengabdian kepada Masyarakat (PKM) yaitu 1) Penerapan PTK bagi guru menggunakan inovasi model pembelajaran Student Centered Learning (SCL). 2) PTK menghasilkan proses pembelajaran aktif dan interaktif sehingga pembelajaran semakin menarik dan tidak membosankan. Metode pelaksanaan menggunakan aspek pengetahuan melalui modul PTK, Aspek Ketrampilan melalui praktek membuat draft PTK, Evaluasi Pelaksanaan. Hasil pelaksanaan PKM yaitu guru dapat menerapkan strategi-strategi atau model-model pembelajaran Student Centered Learning (SCL). Praktek PTK berbasis SCL dapat meningkatkan kualitas pembelajaran. Keterpemahaman peserta dalam mengidentifikasi masalah, merumuskan permasalahan pembelajaran, menyusun kajian pustaka, siklus PTK, Metode PTK, dan langkah-langkah dalam menentukan kesimpulan PTK sudah baik. Peserta sangat antusias dari awal sampai akhir dalam pengerjaan membuat draft proposal PTK.